Plasma amino acids patterns and age of onset of amyotrophic lateral sclerosis. Issue 5 (September 2014) - Cecchi, Matteo; Messina, Paolo; Airoldi, Luisa; Pupillo, Elisabetta; Bandettini di Poggio, Monica; Calvo, Andrea; Filosto, Massimiliano; Lunetta, Christian; Mandrioli, Jessica; Pisa, Federica; Pastorelli, Roberta; Beghi, Ettore; et al.
Abstract The aim of this study was to verify whether abnormalities in plasma amino acid (AA) levels could be biological correlates of the age of onset in amyotrophic lateral sclerosis (ALS). We undertook plasma AA profiling in a large population comprising 117 newly diagnosed ALS patients and 117 matched controls. ALS patients were stratified in early (58 patients aged < 55 years) versus late onset (59 patients aged > 74 years). We applied a rapid and reproducible method for the analysis of AA using amine reactive isotope coded tags in conjunction with liquid chromatography coupled to Multiple Reaction Monitoring-Mass Spectrometry. Results showed that values of only three AA were significantly different in ALS patients and controls. We found lower levels of leucine and higher levels of glutamate and leucine in early-onset ALS compared to their matched controls. In conclusion, different AA patterns related to the ALS age of onset were found, providing insight into possibly aberrant biochemical pathways that might unlock key pathological pathways.